Insulin and glucose sensitivity, insulin secretion and beta-cell distribution in endocrine pancreas of the fruit bat Artibeus lituratus - Protzek, A. O. P.; Rafacho, A. [UNESP]; Viscelli, B. A. [UNESP]; Bosqueiro, José Roberto [UNESP]; Cappelli, A. P.; Paula, F. M. M.; Boschero, A. C.; Pinheiro, E. C. (Elsevier B.V., 2010)
The fruit bat Artibeus lituratus absorbs large amounts of glucose in short periods of time and maintains normoglycemia even after a prolonged starvation period. Based on these data, we aimed to investigate various aspects related with glucose homeostasis analyzing: blood glucose and insulin levels, intraperitoneal glucose and insulin tolerance tests (ipGTT and ipITT), glucose-stimulated insulin secretion (2.8, 5.6 or 8.3 mmol/L glucose) in pancreas fragments, cellular distribution of beta cells, and the amount of pAkt/Akt in the pectoral muscle and liver. Blood glucose levels were higher in fed bats (6.88 +/- 0.5 mmol/L) than fasted bats (4.0 +/- 0.8 mmol/L), whereas insulin levels were similar in both conditions. The values of the area-under-the curve obtained from ipGTT were significantly higher when bats received 2 (5.5-fold) or 3 g/kg glucose (7.5-fold) b.w compared to control (saline). These bats also exhibited a significant decrease of blood glucose values after insulin administration during the iplTT. Insulin secretion from fragments of pancreas under physiological concentrations of glucose (5.6 or 8.3 mmol/L) was similar but higher than in 2.8 mmol/L glucose 1.8- and 2.0-fold, respectively. These bats showed a marked beta-cell distribution along the pancreas, and the pancreatic beta cells are not exclusively located at the central part of the islet. The insulin-induced Akt phosphorylation was more pronounced in the pectoral muscle, compared to liver. The high sensitivity to glucose and insulin, the proper insulin response to glucose, and the presence of an apparent large beta-cell population could represent benefits for the management of high influx of glucose from a carbohydrate-rich meal, which permits appropriate glucose utilization. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Artibeus lituratus; Fruit bat; Insulin action; Insulin and glucose sensitivity; Islets and beta-cell distribution